Evaluating the presence versus absence of the reinforcer during extinction. Issue 3 (12th May 2014) - Castillo, Mariana I.; Borrero, John C.; Mendres‐Smith, Amber E.
Abstract : The purpose of this study was to assess the effects of extinction when the reinforcer was present versus absent. These effects were examined with 2 human operant procedures (i.e., a computer program and a mechanical apparatus) with college students as participants. Discriminable properties of the apparatus appeared to influence responding during extinction. In general, responding during extinction was less likely with the mechanical apparatus when the reinforcer was absent and more likely with the computer program.